A prospective cross-sectional study of laparoscopic subtotal Lind fundoplication for gastro-oesophageal reflux disease – A durable and effective anti-reflux procedure. (January 2015) - Shapey, I.M.; Agrawal, S.; Peacock, A.; Super, P.
Abstract: Introduction: Laparoscopic partial fundoplication for gastro-oesophageal reflux disease (GORD) is reported to have fewer side effects when compared to Nissen fundoplication, but doubts remain over its long term durability in controlling reflux. The aim of this study was to assess outcome of symptoms for all patients presenting with GORD undergoing routine laparoscopic subtotal Lind fundoplication.Materials & Methods: All patients undergoing laparoscopic fundoplication between August, 1999 and November, 2007 performed by a single surgeon were included in the study. The anti-reflux procedure studied was laparoscopic Lind (300°) fundoplication with crural repair in all cases. Patients completed pre and post-operative questionnaires containing validated scoring systems for heartburn, gas bloat, dysphagia and overall patient satisfaction.Results: Over the 100-month period, 320 consecutive patients underwent laparoscopic subtotal Lind fundoplication. Of these, 256 (80%) replied to the questionnaire at a mean of 31 months (range 3–96 months) following surgery. 91.4% of respondents had an improvement in heartburn symptom score with a significant reduction in score from 7.74 preoperatively to 1.25 postoperatively ( p  < 0.001). There was also a significant reduction of mean modified Visick score for reflux control (heartburn and regurgitation) from 3.49 preoperatively to 1.48 after surgery ( p  < 0.001). In total, 22 patients developed recurrent reflux symptoms with half of these reporting their recurrence within two years following surgery. Because of this all were tested with post-operative pH testing, yet only one had a 24-h pH time outside the normal range. Overall patient satisfaction was high with a visual analogue score of 9 and 88% of the patients claimed they would have the operation again.Conclusion: Laparoscopic Lind fundoplication demonstrates excellent reflux control when performed routinely for all patients presenting with GORD. This technique is both durable and efficacious in controlling reflux symptoms. Highlights: Laparoscopic Lind fundoplication: provides excellent reflux control. Laparoscopic Lind fundoplication: is both durable and efficacious in controlling reflux symptoms. Laparoscopic Lind fundoplication: has a low side effect profile compared with other techniques.